1997
DOI: 10.1165/ajrcmb.17.1.2728
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Type II Estrogen Binding Sites and Antiproliferative Activity of Tamoxifen and Quercetin in Human Non-Small-Cell Lung Cancer

Abstract: The antiestrogen tamoxifen is thought to antagonize the effects of estrogens by competing with them for estrogen receptor (ER) binding. However, tarnoxifen can also reverse multidrug resistance, synergize with cisplatin cytotoxicity, and inhibit growth in ER-negative lung cancer cells. In addition to ERs, rat and human target tissues contain a second binding macromolecule termed the type II estrogen binding site (type II EBS). It has been shown that tamoxifen and flavonoids, a widely distributed class of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 32 publications
1
49
0
3
Order By: Relevance
“…Curcumin is cytostatic in several hormone-dependent (MCF-7 and T-47D) and -independent (SK-BR3, BT-20 and MDA231) breast-tumour cell lines (Mehta et al 1997), while genistein and quercetin, in addition to their antiproliferative action, appear to alter the metastatic potential of rat breast adenocarcinoma cells, measured as a reduced ability to migrate within a collagen matrix (Lu et al 1996). Quercetin inhibits tritiated thymidine uptake and proliferation in several non-small-cell lung carcinoma cell lines and reduces bromodeoxyuridine incorporation in primary lung tumour slices (Caltagirone et al 1997). Quercetin also inhibits ML-3 murine hepatoma cell growth (Chi et al 1997).…”
Section: Cancer Cells In Vitromentioning
confidence: 99%
“…Curcumin is cytostatic in several hormone-dependent (MCF-7 and T-47D) and -independent (SK-BR3, BT-20 and MDA231) breast-tumour cell lines (Mehta et al 1997), while genistein and quercetin, in addition to their antiproliferative action, appear to alter the metastatic potential of rat breast adenocarcinoma cells, measured as a reduced ability to migrate within a collagen matrix (Lu et al 1996). Quercetin inhibits tritiated thymidine uptake and proliferation in several non-small-cell lung carcinoma cell lines and reduces bromodeoxyuridine incorporation in primary lung tumour slices (Caltagirone et al 1997). Quercetin also inhibits ML-3 murine hepatoma cell growth (Chi et al 1997).…”
Section: Cancer Cells In Vitromentioning
confidence: 99%
“…The anti-inflammatory and antioxidant properties of flavonoids make them likely candidates for evaluation for the treatment of inflammatory diseases including pulmonary diseases [1][2][3][4]. In addition, flavonoids afford cellular protection by inhibiting enzymes involved in cell proliferation and modulating the expression of proteins associated with apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of studies with conflicting data regarding ERa and ERb expression in human lung cancer and in lung cancer cell lines (Croxtall et al 1994, Caltagirone et al 1997, Omoto et al 2001, Radzikowska et al 2002, Stabile et al 2002, 2005, Hershberger et al 2005 and only two studies directly comparing ER expression in lung cancer specimens and cell lines in males and females (Fasco et al 2002, Mollerup et al 2002. One study reported similar levels of ERa and ERb in females and males (Mollerup et al 2002).…”
Section: Introductionmentioning
confidence: 99%